Efficacy of Organic Farming Against Charcoal Rot of Chickpea (CICER arietinum L.) - Sundus Akhtar; Asma Maryyum; Ayesha Shafqat; Sajida Sharif; Fahad Riaz (BioScientific Review, 2026)
Charcoal rot disease, caused by Macrophomina phaseolina Goid., significantly impacts chickpea (Cicer arietinum L.) production in Pakistan. This study evaluated the efficacy of farmyard manure (FYM) as an ecofriendly management strategy. FYM treatments (0.5%, 1%, 1.5%, and 2%) were applied to M. phaseolina-inoculated soil (positive control), and their effects on disease severity, plant growth, and biochemical parameters were assessed. Results showed that FYM significantly (p £ 0.05) reduced disease infestation in positive control up-to 70%. Moreover, the incorporation of FYM in the soil with M. phaseolina enhanced the physiological traits (total chlorophyll content and soluble sugar (SS)) by 40 to 64% in comparison with positive control. Furthermore, the antioxidant enzyme activities significantly (p £ 0.05) enhanced in C. arietinum, that is, 3 to 4 folds as compared to positive control. Likewise, physiological parameters, for instance, the root and shoot length (SL) and fresh and dry biomass of tested plant significantly (p £ 0.05) increased (up to 70%) in comparison with positive control. The findings suggested that FYM is a cost-effective, sustainable, and environmentally-friendly option for managing charcoal rot disease in chickpea, offering a promising alternative to chemical fungicides.